2020
DOI: 10.52627/ijeam.v2i2.37
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Mutu Perguruan Tinggi Pesantren Melalui Iso 21001 : 2018

Abstract: Higher education has a vital role in nation-building, it is a means to realize intellectuals in order to organize the life of an established nation. This paper aims to explore efforts to improve the quality of pesantren colleges through ISO 21001: 2018 in producing quality, skilled, and professional generations. The method used in this research is a qualitative approach. The informants in this study consisted of leaders, heads of institutions, and faculty leaders. Data collection techniques are carried out usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This is also supported by (Kayyali, 2021). ISO 21001 should also be adopted by Pesantren College in Indonesia to transform the college in the era of Industrial Revolution IR 4.0 (Tohet & Eko Cahyono, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…This is also supported by (Kayyali, 2021). ISO 21001 should also be adopted by Pesantren College in Indonesia to transform the college in the era of Industrial Revolution IR 4.0 (Tohet & Eko Cahyono, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…In addition to the curriculum, enhancing quality is also crucial in implementing institutional integration. The findings of a study conducted by Tohet & Cahyono (2020) indicate that students are attracted to high-quality universities. This affirms that enhancing quality is a vital element in the integration of Islamic boarding schools and colleges.…”
Section: Ma'had Darul Qur'an Wal Hadith Institutional Integration -Hi...mentioning
confidence: 99%
“…Integrating Islamic boarding schools with colleges is a strategic measure aimed at modernizing Islamic education in Indonesia. This process entails making modifications to the curriculum, embracing contemporary teaching methodologies, and implementing structural reforms in the management and operations of Islamic boarding schools (Bashori, 2017;Tohet & Cahyono, 2020). Although this development signifies advancement, there are also apprehensions over its influence on Islamic identity and spirituality within the realm of education.…”
Section: Ma'had Darul Qur'an Wal Hadith Institutional Integration -Hi...mentioning
confidence: 99%
“…According to the literature, PTKIS institutions managed by pesantren are referred to Pesantren-based Higher Education (Zarkasyi, 2017;Bali, 2017). Pesantren-based Higher Education (PTBP) integrated both higher education and pesantren education systems (Zarkasyi, 2017) to respond to global challenges (Thoyib et al, 2020;Tohet & Eko, 2020;Bali, 2017) and is alleged as an ideal Islamic higher education model considering its critical role in the process of integration-interconnection of science and Islamic teaching (Halil & Anwar, 2016;Tohet & Eko, 2020;Husni, 2017). However, despite the fact that many Muslim scholars claimed PTBP as an ideal Islamic higher education, the fact showed that PTBP institutions' inability (as part of PTKIS) to compete with other higher education is undeniable.…”
Section: Introductionmentioning
confidence: 99%